2006
DOI: 10.3171/ped.2006.104.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative incidence of radiation-induced cavernomas in long-term survivors of medulloblastoma

Abstract: Cavernomas are common after cranial irradiation in children, and their incidence increases over time. Most of these lesions follow a benign course and do not require intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 19 publications
3
55
0
3
Order By: Relevance
“…Vascular telangiectasias are reported more frequently in patients after CNS irradiation. 2527 Parenchymal radiation-associated MR imaging changes typically manifest as progressive, mild to moderate T2 prolongation in the periventricular white matter, 25 which may be the result of vascular abnormalities leading to parenchymal ischemia and white matter degeneration. It is not clear, however, whether similar mechanisms cause the white matter changes seen in older patients with A-T.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular telangiectasias are reported more frequently in patients after CNS irradiation. 2527 Parenchymal radiation-associated MR imaging changes typically manifest as progressive, mild to moderate T2 prolongation in the periventricular white matter, 25 which may be the result of vascular abnormalities leading to parenchymal ischemia and white matter degeneration. It is not clear, however, whether similar mechanisms cause the white matter changes seen in older patients with A-T.…”
Section: Discussionmentioning
confidence: 99%
“…[3489] Venous restrictive disease has been postulated to be a consequence of impaired venous flow caused by radiation change. This impairment increases venous pressure and may lead to the formation of cavernous hemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions usually appear 8–10 years later within brain tissue that was included in radiation fields. [34]…”
Section: Introductionmentioning
confidence: 99%
“…Mutations have also been blamed for cavernoma formation 3 11. Their latency period varies, and their incidence reportedly increases over time 12. Poussaint et al reported a series of 20 pediatric patients with intracranial neoplasia in whom delayed intracranial haemorrhage developed after cranial irradiation or radiation combined with systemic or intrathecal chemotherapy.…”
Section: Discussionmentioning
confidence: 99%